Acute induction of interleukin-6 and biphasic changes of serum complement C3 by carrageenan in mice. Issue 3 (1998) - Tateda, K.; Matsumoto, T.; Yamaguchi, K.
Abstract : Carrageenan has been widely used as an irritant to evoke inflamm ation in animals or to selectively deplete m acrophages in vivo . Although precise understanding of carrageenan activity is a prerequisite for the experimental use of this polysaccharide, the effects of this agent on host-biological systems are still poorly understood. We investigated the effect of carrageenan on serum concentrations of complement C3 and interleukin (IL)-6, a potent complementinducing factor. Intraperitoneal administration of carrageenan (4 mg) in mice resulted in an initial fall in serum C3 (70% of control, p < 0.05 ) between 3 and 6 h, but was followed by a significant rise (180% of the control, p < 0.05 ) at 24 h. Prior to the rise in complement C3, a sharp peak of serum IL-6 was observed at 6 h after carrageenan treatment. These results indicate potential of carrageenan to enhance host complement systems, which may be associated with, at least in part, an acute induction of IL-6.